Case Report: Guillain-Barré Syndrome Characterized by Severe Headache Associated With Metabotropic Glutamate Receptor 5 Antibody - Yan, Weiqian; Zhao, Cheng; Zhang, Hainan; Hu, Zhiping; Wang, Chunyu (Frontiers in Immunology, 2022)
Autoantibodies to metabotropic glutamate receptor 5 (mGluR5) are known to be the cause of autoimmune encephalitis, particularly limbic encephalitis, closely related to Hodgkin’s lymphoma (HL). The involvement of peripheral neuropathy is rarely reported. In our case, mGluR5 antibody was found in a Guillain-Barré syndrome (GBS) patient accompanied by severe headache but without neuropsychiatric manifestations or HL. Presenting with severe headache, the patient developed progressive bilateral limb weakness, areflexia, and cranial nerve involvement consisting of eye movement disorder, restricted mouth opening and chewing, bilateral facial paralysis and bulbar palsy. Cerebrospinal fluid (CSF) revealed elevated CSF protein level and normal cell count, known as “albumino-cytological dissociation”. Oligoclonal IgG bands were found in both the CSF and serum. Electrophysiological studies revealed symmetrical sensory and motor neuropathy with a mixture of axonal and demyelinating features. Brain and spinal cord magnetic resonance imaging (MRI), as well as the electroencephalogram, were normal. The mGluR5 antibody was positive in both serum and CSF with a Cell-Based Assay (CBA). The patient responded well to intravenous gammaglobulin therapy, correlated with a reduction of mGluR5 antibody titer from 1:30 to 1:10 in the serum. After 6 months, the patient recovered completely without any sign of recurrence or neoplasm. This first case of mGluR5 antibody-associated GBS accompanied by severe headache shows that mGluR5-associated disorders are not limited to manifestations of limbic encephalitis and HL.